2020
DOI: 10.3390/cells9010177
|View full text |Cite
|
Sign up to set email alerts
|

SSEA3 and Sialyl Lewis a Glycan Expression Is Controlled by B3GALT5 LTR through Lamin A-NFYA and SIRT1-STAT3 Signaling in Human ES Cells

Abstract: B3GALT5 is involved in the synthesis of embryonic stem (ES) cell marker glycan, stage-specific embryonic antigen-3 (SSEA3). This gene has three native promoters and an integrated retroviral long terminal repeat (LTR) promoter. We found that B3GALT5-LTR is expressed at high levels in human ES cells. B3GALT5-LTR is also involved in the synthesis of the cancer-associated glycan, sialyl Lewis a. Sialyl Lewis a is expressed in ES cells and its expression decreases upon differentiation. Retinoic acid induced differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…Notably, the glycosyltransferase pattern expressed in native tissues is available only for the colon [24,40,41,46,47] and pancreas [47][48][49], but not for other gastrointestinal organs, such as the stomach and the bile ducts (Table 1). Moreover, the available data suggest that the glycosyltransferase regulation is tissue-specific and affected by mechanisms that operate in only native tissues [28,50,51], making the studies performed in cell lines poorly representative. [47][48][49] Tissue antigens by immunofluorescence/dot-blot CA19.9, Lea, and Leb detected in both normal and cancerous ducts (luminal staining), no one in normal acinar cells or poorly differentiated cancer cells [47] Tissue antigens by immunohistochemistry CA19.9 detected in cancer (frequent cytoplasmic staining) better than in normal ducts (luminal staining) […”
Section: Biosynthesis Of Type 1 Chain Lewis Antigens In Gastrointestimentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, the glycosyltransferase pattern expressed in native tissues is available only for the colon [24,40,41,46,47] and pancreas [47][48][49], but not for other gastrointestinal organs, such as the stomach and the bile ducts (Table 1). Moreover, the available data suggest that the glycosyltransferase regulation is tissue-specific and affected by mechanisms that operate in only native tissues [28,50,51], making the studies performed in cell lines poorly representative. [47][48][49] Tissue antigens by immunofluorescence/dot-blot CA19.9, Lea, and Leb detected in both normal and cancerous ducts (luminal staining), no one in normal acinar cells or poorly differentiated cancer cells [47] Tissue antigens by immunohistochemistry CA19.9 detected in cancer (frequent cytoplasmic staining) better than in normal ducts (luminal staining) […”
Section: Biosynthesis Of Type 1 Chain Lewis Antigens In Gastrointestimentioning
confidence: 99%
“…Notably, the glycosyltransferase pattern expressed in native tissues is available only for the colon [ 24 , 40 , 41 , 46 , 47 ] and pancreas [ 47 , 48 , 49 ], but not for other gastrointestinal organs, such as the stomach and the bile ducts ( Table 1 ). Moreover, the available data suggest that the glycosyltransferase regulation is tissue-specific and affected by mechanisms that operate in only native tissues [ 28 , 50 , 51 ], making the studies performed in cell lines poorly representative.…”
Section: Biosynthesis Of Type 1 Chain Lewis Antigens In Gastrointementioning
confidence: 99%
See 1 more Smart Citation
“…B3GALT5 is essential for the synthesis of stages specific embryonic antigen-3 (SSEA3), the pentasaccharide precursor of Globo H. This gene has three native promoters and an integrated retroviral long terminal repeat (LTR) promoter. A recent study showed that B3GALT5-LTR is regulated by lamin A-NFYA and SIRT1-STAT3 signaling [84]. Further studies are needed to explore the involvement of transcription factors in the regulation of Globo H antigen expression during tumorigenesis.…”
Section: Biological Roles Of Globo H In Cancermentioning
confidence: 99%
“…It has been shown to act in the formation of type 1 Lewis antigens of pancreatic and colorectal epithelial cells (Isshiki et al, 1999). B3GALT5 is highly expressed in the GI tract and embryonic stem cells and to a lesser extent in the central nervous system (Cai et al, 2020). Expression levels of B3GALT5 and its lncRNAs appear to influence colon cancer metastasis and are a predictor of survival in hepatocellular carcinoma (Kuo et al, 2017; Wang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%